The "revolt of the ferries": on performative silencing and protest immateriality in contemporary (in) visibility of urban outskirts - Raposo, Paulo (2016)
In this article I intend to think the intersection between public space, political performances and media transmission from the point of view of the anthropology of performance. Through the reading of an urban riot uprising which took place in 1959 in Niterói, The Revolt of the Ferries, I proposed to the participants in a workshop at the Fluminense Federal University in November 2014, a performative installation to revisit the riot memory and, above all, to reenact it from a political point of view considering the recent conflicts associated with the Free Pass Movement in Brazil. I start by analyzing a set of imagery of recent protests in Portugal, the United States, Spain and Brazil in order to find out similar traits in the performance of those political mobilization and in the answer given by the dominant power. “Artivism” emerges as a concept to be explored in contemporary political protests. Throughout the article I will try to highlight its activist performativity, its “carnavalization” effects and its possible articulations between repertoires and archives.Translation: Barbara Theoto Lambert